PENGARUH MASA KERJA DAN PENDIDIKAN GURU TERHADAP KINERJA GURU SDN SUKABUMI 10 KOTA PROBOLINGGO - Rohmat Hasan (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2015)
This research aims to know the influence of years of service and educational background on teachers’ working performance at SDN Sukabumi 10 Probolinggo. Forty (40) students were invoked in this research as respondents. As a result, it showed that there was significant influence of years of service, educational background, and years of service and educational background simultaneously on teachers’ working performance at SDN Sukabumi 10 Probolinggo.